2003
DOI: 10.1177/0741088303260504
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Graders Composing Scientific Explanations About the Effects of Pollutants

Abstract: Explanation as a genre may support children's reasoning and understanding particularly effectively. In this study, 20 fourth graders were given the task of explaining the effects of a pollutant on an ecosystem to third graders. Before writing, they completed a commercially developed science unit, instruction in reading and writing an explanation, and text reading. An analysis of their writings revealed that all children used rhetorical devices to connect with third-grade readers. Sixteen children synthesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
16
0
3
Order By: Relevance
“…This possibility has also been noted by Boscolo and Borghetto (2002) and Chambliss et al (2003). It would be particularly interesting to examine this possibility with older students, who could compare and contrast complex subjects, such as authors, texts, or theories.…”
Section: Implications For Future Researchmentioning
confidence: 85%
See 2 more Smart Citations
“…This possibility has also been noted by Boscolo and Borghetto (2002) and Chambliss et al (2003). It would be particularly interesting to examine this possibility with older students, who could compare and contrast complex subjects, such as authors, texts, or theories.…”
Section: Implications For Future Researchmentioning
confidence: 85%
“…Students were asked to work in pairs (as suggested by Stead, 2002) to rate these samples, and the ratings were discussed as a class. Teachers modeled how to create the planning in a table (IAPN, which is presented in section 2.4.1), and how to use it to write a text (in keeping with Bereiter & Scardamalia, 1987;Chambliss et al, 2003;Englert et al, 1991;Graham & Harris, 1997;Pressley, 2003;Pressley et al, 1995;Wong, 2000;Zimmerman & Risemberg, 1997). Students also had the opportunity to plan and write independently (as suggested by Harris & Graham, 1996).…”
Section: The Present Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, codes were assigned for the function they serve in the text or the meaning or the idea they convey in the text. Similar strategies were previously used by researchers to analyze student writings (Chambliss et al 2003;Keys 1999). Some code units were, evidence, cause, effect, elaboration, inference and hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…There may be a mismatch between the cognitive work required for students to succeed in the biology curriculum and the types of reasoning with which adolescents readily engage. Indeed more recent research showed that scaffolding students' scientific explanations through various ways, such as explicit teaching of explanatory genre (Chambliss et al 2003), or through written explicit guidance in laboratory worksheets that identifies explanatory elements (e.g. claims, evidence, McNeill et al 2006) or through computer software that provides explanation guides (Sandoval 2003), results in better student explanations.…”
mentioning
confidence: 99%